Bankruptcy Probability Risk and Stock Returns in Emerging Stock Exchange Markets – South East Asian Evidence - Luong, Cong Khanh (2015)
Distress puzzle is referred as whether bankruptcy risk is related to systematic risk or unsystematic risk. If bankruptcy is at least partly related to systematic risk, it suggests that investors should be rewarded with higher stock return for bearing higher distress risk. Many researchers attempt to investigate this financial distress puzzle. However, this puzzle is still inconclusive. Although there is abundant literature explaining financial distress puzzle, there is a limited research in the existing literature investigating companies in emerging markets. The main purpose of this work is to contribute to the literature of financial distress puzzle in the case of South East Asian emerging markets by testing the relationship between bankruptcy risk measured by Altman’s Z-score and stock return. Using panel data methodology with univariate and multivariate technique, we find that there is a significant positive relationship between Altman’s Z-score and stock return. Furthermore, when controlling additional book-to-market effect and size effect, this positive relation appears to be diluted. In general, this study support the view of bankruptcy risk might be related to unsystematic in respect with stocks of companies listed on South East Asian emerging markets.